2001
DOI: 10.1046/j.1365-2443.2001.00399.x
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus RNA polymerase PA subunit is a novel serine protease with Ser624 at the active site

Abstract: Background: Influenza virus RNA polymerase is a multifunctional enzyme that catalyses both transcription and replication of the RNA genome. The function of the influenza virus RNA polymerase PA subunit in viral replication is poorly understood, although the enzyme is known to be required for cRNA 3 vRNA synthesis. The protease related activity of PA has been discussed ever since protease-inducing activity was demonstrated in transfection experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 73 publications
1
48
0
Order By: Relevance
“…1A). This inhibitory effect of PA has been described before and is probably due to the expression of the PA-X protein (16,22,43,44). Coexpression of increasing amounts of PB2 and, to some extent, of NP counteracted the inhibition of viral polymerase activity by Mx1 (Fig.…”
Section: Pb2supporting
confidence: 66%
“…1A). This inhibitory effect of PA has been described before and is probably due to the expression of the PA-X protein (16,22,43,44). Coexpression of increasing amounts of PB2 and, to some extent, of NP counteracted the inhibition of viral polymerase activity by Mx1 (Fig.…”
Section: Pb2supporting
confidence: 66%
“…Hara et al reported that the PA subunit is in fact a chymotrypsin-like protease having its catalytic site at serine 624 (14). However, by mutation analysis, we observed that the ability of PA to induce in vivo protein degradation lay within the 247 N-terminal amino acids of the protein, threonine 157 being involved in this activity (32,39).…”
mentioning
confidence: 60%
“…47,68 The fold of the endonuclease domain and its biochemical properties are similar to those of type II restriction endonucleases. 63,66 In addition of the endonuclease active site, protease activities have been associated to the PA subunit of the polymerase [69][70][71] and a correlation has been reported between such an activity and the capacity of the polymerase to replicate. 72,73 The mechanism by which the polymerase subunits interact, the site where the trimeric complex is formed and its transport to the nucleus have been analysed in detail.…”
Section: To Switch or Not To Switchmentioning
confidence: 99%